Decolonizing the Gospel of Love in Africa - Orbih, William I. (Religions, 2024)
The violence of missionary agents on Africans contradicted the gospel of Christ’s redemptive love, which they preached. In response to the contemporary manifestations of the violence and dehumanization of “colonial love”, this article proposes the decolonization of the gospel of love, both as theological hermeneutic and a moral imperative in the African Church. In the parable of the Good Samaritan, Jesus commands us to recognize every human being as a neighbor. Within a colonial context, this means rejecting the dualistic logic of colonial love, its segregation, dehumanization, and violence.